Changes in the clinical features of child and adolescent psychiatric inpatients: a nationwide time-trend study from Finland. (17th August 2016) - Kronström, Kim; Ellilä, Heikki; Kuosmanen, Lauri; Kaljonen, Anne; Sourander, Andre
Abstract : Background : Few studies have focused on the recent trends in clinical features child and adolescent inpatient. Aims: This study focuses on the change in the characteristics of child and adolescent psychiatric inpatients in Finland. Methods: The data collection was carried out on selected study days in 2000 and 2011. Questionnaires were sent to the psychiatrists of all child and adolescent wards in Finland.Results : By comparing the data obtained in 2000 (n = 504) and 2011 (n = 412), several changes were found: the percentage of girls in adolescent wards grew and the diagnoses of depression, anxiety disorders, attention deficit hyperactivity disorder and eating disorders increased. In contrast, the diagnoses of psychosis and conduct or oppositional disorders decreased. General functioning was evaluated with the Childreńs Global Assessment Scale (CGAS). There were no changes in the distribution of CGAS scores among child inpatients, whereas among adolescents the share of inpatients with lowest CGAS scores (1–30) increased significantly. The mean length of stay dropped.Conclusions : The growing percentage of girls in adolescent wards is associated with an increase in diagnoses that are more prevalent among girls than boys, namely depression, anxiety, and eating disorders. The changes in the distribution of diagnoses may be due to changes in diagnostic or referral practices, or reflect true changes in the prevalence of disorders among children and adolescents in need of inpatient treatment. The share of adolescent inpatients with the poorest general functioning has increased. The observed shortening in inpatient treatment time seems to be a result of changes in treatment practices.